The progression of sustainable development goals in tourism: A systematic literature review of past achievements and future promises - Hafiz Muhammad Usman Khizar; Aurangzaib Younas; Satish Kumar; Ahsan Akbar; Petra Poulova (Journal of Innovation & Knowledge (JIK), 2023)
The UN 2030 agenda for global sustainable development has huge connotations for the theory, practice, and policy of tourism. This study comprehensively evaluates extant scholarly publications related to the United Nations Sustainable Development Goals (SDGs) in existing tourism scholarship. This review also evaluates existing research to identify knowledge gaps in the literature and to set future research agendas in tourism research to accelerate the progress of the UN SDGs. Doing so, we have utilized the systematic literature review (SLR) technique to identify, select, review, and evaluate extant scholarly publications on this topic. The Web of Science database was used to discover research publications using the keywords, tour* AND (sdg* OR 'sustainable development goal*' OR 'UNSDG*' OR 'UN agenda' OR 'global agenda' OR 'agenda 2030' OR 'agenda-2030'). A sample of 88 relevant empirical articles were systematically selected and reviewed. The findings are categorized into three main sections: (i) descriptive profiling of existing research, (ii) literature synthesis, and (iii) existing knowledge gaps and future research agenda. Given that the SLRs are rarely used in the realm of sustainable tourism and SDGs, this review provides a knowledge base of what is already known to further extend the scholarly debate on the role of tourism in achieving the SDGs. In particular, we highlight theme-based knowledge gaps and limitations in the existing literature and suggest future research agendas by presenting several potential research questions.
Keywords: Z30; Z32; 650; Sustainable development goals; UN SDGs; sustainable tourism; systematic literature review